A Feasibility Study on Canned Mushrooms Little Smurfs Inc. - Dolor, Katherine; Jaimini, Juris Lynn.; Marquez, Diana (Diliman, Quezon City College of Engineering, 2002)
The culture mushroom is gaining popularity in the Philippines. The market for mushrooms continues to grow due to interest in their nutritional and health benefits. Mushroom is a delicacy and is readily accepted as a vegetable. Its present cultivation in this country is limited, perhaps due to the insufficiency of planting materials and the limited local knowledge about its culture. Processing of mushrooms is one of the industries being encouraged by the Board of Investments. It is included in the 6th Investment Priorities Plan under processed vegetables. Mushroom processing may offer opportunity to those willing to develop a commercial operation as an additional enterprise for farms and rural communities. The canned mushrooms are named by the proponents as Cream of the Crop Mushrooms. Furthermore, the market study identified two potential markets for canned mushrooms which are local households and hotels, restaurants and fast food chains and NCR is its target market area. A comprehensive marketing strategy worth P271,000.00 for the first year was prearranged. In the Technical Study, the proponents were able to gather much needed information regarding the processes, operations and projected costs of all relevant technical inputs needed to produce the mushrooms. Three major processes will be done in the plant. These are Composting of Rice Straw, Canning of mushroom. Preparing the spawn is a highly technical task and the company will buy the spawns rather than to produce it themselves. Little Smurfs Incorporated shall consider the suppliers of raw materials such as rice straw, composting chemicals, tin cans and labels with the cheapest selling prices per raw material as its regular suppliers. Secondary suppliers will also be noted in the event of unavailability of stock from primary suppliers. All canning machinery and transportation equipment will be bought brand new from selected local suppliers except for the delivery vans and the forklift. This plan was chosen since in the case of delivery vans and forklift it will be cheaper to acquire second hand equipment than a brand new one. Since the company has a limited capital, the proponents have deemed it wiser to buy brand new machineries for equipment used in the actual canning process. The three major processes will require 20 workers for the first year. Six are assigned to rice composting and mushroom growing. Fourteen are assigned to mushroom canning and one technician is assigned to repair the machines. In selecting the production plan, three alternatives were considered by the group. These alternatives are as follows: Alternative 1: Production at 7 days/week, Alternative 2: Production at 6 days/week, Alternative 3: Production at 5 days/week. Each alternative was evaluated based on the number of beds to be used during mushroom growing, cost of labor, cost of utilities and cost of rice straw composting. Alternative 1 which has the least total cost was chosen at the most attractive alternative. The plant location was chosen based on sufficient area for expansion, fresh water availability, temperature, transportation accessibility, proximity to suppliers and resources, real estate costs and taxes, and waste disposal system. Little Smurf's Inc. will be located in General Trias, Cavite and will occupy a total land area of 5000 sq meters. The total project cost of Little Smurf's Inc., amounts to Php 12,131,309.90. This is the amount needed by the proponents of the study to start the project. Organization and Management study indicated that the corporation type is the best form of ownership for the company. The corporate form is most suitable when a relatively large amount of capital must be raised from a large number of contributors. The corporate form permits easy transferability of ownership interest because ownership interests can be divided into shares of stock. Other relevant features of a corporation are: greater formality in the conduct of business affairs as required by the Corporation Code and by the Securities and Exchange Commission; fixed tax rate at 32% of net tax income; stability due to ease of change of ownership interests; and limited liability of owners. Little Smurfs Incorporated will primarily integrate a vertical structure in its organizational structure since its production process basically involves a high volume, low variety and repetitive in nature. The organization will be divided into five departments with each department having a manager heading his/her respective department: production, finance, marketing, personnel, sales and distribution, and purchasing. For the financial study Little Smurf's has identified an initial total project cost of P12,131,309.90. A total amount of P2,131,309.90 will be loaned from DBP with an interest rate of 12 %, with a 60% collateral and a five-year payment period. The criterion used in evaluating the different loaning institutions includes the interest rate, the payment period, and the grace period for the loan. The company will be offering capital stock worth P10,000,000.00 Little Smurf's Incorporated will issue stocks with low par value to attract small time investors. Common stock will cost P50.00 per share and preferred stick at P60.00 per share. Using sensitivity analysis and financial ratios, the project was assessed. From the results of the different tests, it was concluded that it is financially feasible. Its payback period is 0.68 years of 9 months approximately. The IRR computed is 62.45%, which is greater than the MARR used, which is 16%. The net present value of the venture is Php 18,729,354.92. Since it is greater than zero, then we can say than mushroom canning is an acceptable venture. In conclusion, the socio-economic study yielded several benefits. For the general public, it provides benefits such as nutritional value, high quality product and promotion of environmental awareness. For the local community, the establishment of a new company, such as Little Smurf's Incorporated, will undoubtedly open new opportunities for employment. For the government, the establishment of Little Smurfs Incorporated will greatly contribute to the economic status of the Philippines through the payment of taxes. For the local industries, the purchase of equipments worth Php 1,782,650.00 and office furniture worth Php 109,474.00 will be earned for the first year. Based on the five different studies on the feasibility of mushroom production and canning in the Philippines, it can be concluded that the project is deemed feasible.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Little Smurfs Inc; Mushroom industry; Canned mushrooms; Participatory monitoring and evaluation (Project management)